Reflections on the Song “Ya Sudahlah” by Bondan Prakoso & Fade2Black as a Positive Affirmation for Generation Z Listeners - Desti Viandari Rossa; Farida Nurfalah (Journal Of Social Science (JoSS), 2026)
Gen Z is a generation that is highly tech-savvy but prone to anxiety due to a quarter-life crisis. Previous research has not specifically examined Gen Z experiencing a quarter-life crisis or the relationship between song lyrics and positive affirmations based on stress-coping theory and positive psychology. This study, Reflections On The Song “Ya Sudahlah” By Bondan Prakoso & Fade2Black As A Positive Affirmation For Generation Z Listeners, was conducted to analyze the song “Ya Sudahlah” as a form of positive affirmation and to identify the nature of positive affirmations among Gen Z. The study employed a qualitative approach using descriptive phenomenology, involving interviews, song analysis, documentation, and a literature review of books and journals. Data validity was ensured through source triangulation. The results of the study indicate that the song “Ya Sudahlah” provides a new perspective for all informants in viewing life. Informants became more accepting and viewed failure as an integral part of life that cannot simply be discarded. This song also enables informants to think more clearly when solving problems. Additionally, informants are better able to control their emotions, focus on what they can do, and learn from difficult experiences. Overall, this song provides positive affirmation in the form of motivation, validation, and a reminder that they are not alone in facing problems.